2010
DOI: 10.1523/jneurosci.5806-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Neural Cell Adhesion Molecule-Associated Polysialic Acid Regulates Synaptic Plasticity and Learning by Restraining the Signaling through GluN2B-Containing NMDA Receptors

Abstract: The neural cell adhesion molecule (NCAM) is the predominant carrier of α2,8 polysialic acid (PSA) in the mammalian brain. Abnormalities in PSA and NCAM expression are associated with schizophrenia in humans and cause deficits in hippocampal synaptic plasticity and contextual fear conditioning in mice. Here, we show that PSA inhibits opening of recombinant NMDA receptors composed of GluN1/2B (NR1/NR2B) or GluN1/2A/2B (NR1/NR2A/NR2B) but not of GluN1/2A (NR1/NR2A) subunits. Deficits in NCAM/PSA increase GluN2B-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 66 publications
9
87
1
Order By: Relevance
“…NRCAM-PSA-expressing interneurons in mice show reduced dendritic spine numbers, decreased arborization, and changes in the synaptic connectivity (54). A study of cultured hippocampal neurons showed that PSA-NRCAM is required for N-methyl-D-aspartate (NMDA) receptor-dependent LTP and acts as an antagonist at N2RB-subunit-bearing NMDA receptors, preventing glutamate-induced cell death (55,56). The role of NRCAM at NMDA receptors is of particular interest given that NMDA receptor hypofunction in the prefrontal cortex is one of the leading schizophrenia hypotheses and has been linked to the cognitive symptoms and oscillatory disturbances associated with the disease (57).…”
Section: Resultsmentioning
confidence: 99%
“…NRCAM-PSA-expressing interneurons in mice show reduced dendritic spine numbers, decreased arborization, and changes in the synaptic connectivity (54). A study of cultured hippocampal neurons showed that PSA-NRCAM is required for N-methyl-D-aspartate (NMDA) receptor-dependent LTP and acts as an antagonist at N2RB-subunit-bearing NMDA receptors, preventing glutamate-induced cell death (55,56). The role of NRCAM at NMDA receptors is of particular interest given that NMDA receptor hypofunction in the prefrontal cortex is one of the leading schizophrenia hypotheses and has been linked to the cognitive symptoms and oscillatory disturbances associated with the disease (57).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed the importance of GluN modulation by cell adhesion molecules such as the neural cell adhesion molecule (NCAM) (Hammond et al, 2006;Kochlamazashvili et al, 2010). NCAM, which belongs to the Ig superfamily of cell adhesion molecules, is involved in diverse functions during neurodevelopment (Maness and Schachner, 2007), and it is func-tionally modified by long homopolymers of ␣2,8-linked sialic acid residues known as polysialic acid (PSA) (Rutishauser, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Polysialylation of NCAM has also been shown to regulate neuritogenesis (Seidenfaden, 2006), and axonal growth (Doherty et al, 1990;Zhang et al, 1992) synaptic plasticity and activity-dependent cell remodeling, which has been extensively reviewed (Bonfanti & Theodosis, 2009;Muller et al, 2010;Kochlamazashvili et al, 2010). The effects of PSA-NCAM on axonal fasciculation and defasciculation in different systems have been reported and seem to depend on a combination of both intrinsic and context/environment dependent effects (reviewed by Durbec & Cremer, 2001).…”
Section: Polysialylation Results In Plasticity At the Cellular Scalementioning
confidence: 99%